Exploring variations in healthcare expenditures: What is the role of practice styles? - Alexander Ahammer; Thomas Schober (Johannes Kepler University of Linz, Department of Economics, 2017)
Variations in the use of medical resources, both across and within geographical regions, have been widely documented. Whenever these variations cannot be explained by differences in patient needs or preferences, they may result in some individuals being over-treated, while others are under-treated, thus raising questions on the equity and efficiency of healthcare systems. One explanation for these variations is differences in medical practice styles; that is, physicians may develop their own treatment patterns based on their beliefs about the efficacy of medical interventions. We use a large administrative data set from Upper Austria to study the practice styles among primary care physicians. We decompose the use of healthcare services into patient characteristics, patient and physician fixed effects, and stochastic health shocks. Physician fixed effects are interpreted as a measure of practice styles, which are then related to observable physician characteristics and to attributes of the local healthcare sector.
Keywords: I11; I12; C23; 330; Health care expenditures; variation; practice styles; physician behavior